Role of Business Analytics in Effective CRM Implementation in Retail Sector: A Cross Sectional Research - Saurav Kumar, Atul Karn, Abhishek Chauhan, Mukesh Singh (Journal of Informatics Education and Research, 2023)
Customer relationship management (CRM) continues to evolve and has undergone significant advancements. Major companies are increasingly leveraging automation and artificial intelligence (AI) technologies to gain insights into buying patterns of customer, enhancement of brand communication, and strengthen connections with customers. CRM is employed by organizations as a set of tools, processes, and technologies for tracking, analysing, and collaborating on customer data through the entire lifecycle of customers. This paper researches into the theoretical foundations of Business Analytics (BA), its integral elements, and the advantages it offers. Businesses can achieve their strategic objectives and attain success through the utilization of BA tools. In today's highly competitive market, retailers are putting a strong emphasis on customer intelligence to not only improve relationships but also cut costs. Business Analytics techniques empower companies to strengthen their understanding of customers, boost their knowledge, and ultimately increase turnover. BA plays a crucial role in delivering enhanced customer experiences, thus strengthening the bond between consumers and brands and enhancing brand uniqueness. A sample of 307 was collected from people working in marketing department of retail sector. The factors that determine the role of Role of Business Analytics in Effective CRM Implementation Retail Sector are Customer Segmentation, Performance Tracking, Personalized Marketing, and Customer Feedback Analysis.